Specificity of translating mood dominants in the short story “Kamizelka” by Boleslaw Prus (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article represents the peculiarities of event modeling in the short story “Kamizelka” by Polish writer Boleslaw Prus. The paper studies the way of artistic event presentation in the short story in terms of its essence, which is subordinated to the mood dominant. The latter is revealed through reconstructing the inner experiences of the characters, which are relevant to the state of sadness and anguish imposed on the memories of tragic past life events. It is noticed that the short story “Kamizelka” contains such features of the novelistic genre as: the presence of a single mood epicenter, dynamism, conciseness, the compactness of the composition, the fraught plot, routine and simultaneously unusual event presentation, a symbolic thing called “kamizelka”. It is determined that the dynamic of the plot in the short story is ensured not only by short and rhythmic sentences, but also by paragraph structuring of the text. The paragraph features in the short story by Boleslaw Prus are aimed at focusing the recipient’s attention on an important moments or episodes that make up the content of the paragraph. In this way, the author tried to increase the tension of the plot and balance the mood of events in the work, modeling the situation of anticipation, warning, as the mood dominant of the text in the short story.
Keywords: mood nodes; author narration; localized plot; mood epicenter